2021
DOI: 10.1089/jwh.2019.8135
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia and Susceptibility to Depressive Symptoms and Fatigue in Diverse Breast Cancer Survivors

Abstract: Background: Nearly 40% of breast cancer survivors have insomnia, yet, information how this condition affects their quality of life is lacking. We examined the association between insomnia and depressive symptoms and fatigue in breast cancer survivors. Methods: Participants were recruited from a community health plan. We conducted a cross-sectional analysis to examine the association between current insomnia (using Insomnia Severity Index [ISI]) and current depressive symptoms (using Inventory of Depressive Sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…Sleep disturbance is prevalent in cancer patients and survivors, and understanding of its connection with the PNI could produce more effective interventions and improve QOL. Although a few groups have published extensive studies on stress and sleep in the context of cancer [ 2 , 68 71 , 72 74 ], few studies have examined the relationship of sleep, distress, and immunity in cancer patients [ 75 77 ] or cancer survivors [ 2 , 78 , 79 ], and none have been focused on cervical cancer patients or survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disturbance is prevalent in cancer patients and survivors, and understanding of its connection with the PNI could produce more effective interventions and improve QOL. Although a few groups have published extensive studies on stress and sleep in the context of cancer [ 2 , 68 71 , 72 74 ], few studies have examined the relationship of sleep, distress, and immunity in cancer patients [ 75 77 ] or cancer survivors [ 2 , 78 , 79 ], and none have been focused on cervical cancer patients or survivors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies after treatment did report a correlation between sleep and fatigue [ 27 ], sleep–fatigue symptom clusters [ 28 ], or found sleep disturbance as a predictor of fatigue [ 29 ]. In adult oncology, an interrelationship between impaired sleep and fatigue in survivors using different methods and in diverse populations has been reported [ 30 , 31 , 32 ]; however, much remains unclear about the specific mechanisms of co-occurring insomnia and fatigue. Since studies in large samples in pediatric oncology are lacking, little information about sleep has been included within recommendations for the surveillance and treatment of cancer-related fatigue in pediatric oncology survivors [ 11 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sleep disorders, such as hypersomnia, short sleep duration, restless legs syndrome, parasomnia, sleep apnea and insomnia, experienced by breast cancer survivors were detected to be associated with decreased physical function and emotional states (including, depressive symptoms and distress), while low sleep quality was observed to be associated with greater levels of anxiety and depression (Cho and Hwang, 2021). However, "sparse population-based data exist about the contribution of insomnia symptoms to occurrence of depressive symptoms in breast cancer survivors" (Haque et al, 2020). A study by Ho et al, (2015) found a correlation between depression, fatigue and sleep quality in both premenopausal and postmenopausal women with breast cancer.…”
Section: Introductionmentioning
confidence: 99%